KEBERADAAN JENIS JENIS BURUNG DI KAWASAN PADANG PADANG PECATU KABUPATEN BADUNG - Suaskara, Ida Bagus Made; Ginantra, I Ketut; Muksin, I Ketut (Bumi Lestari, 2010)
A study on bird species was conducted in January-February 2009 at Padang Padang Pecatu Badung Bali. Explorations methods was utilized to find out bird species which observed in the field. Identification of bird species was undertaken based on (Mackinnon, 1993 ). Their status were determined based on Indonesian Regulation ( PP RI) No. 7, 1999. Interview with community was carried out to know the bird species captured. Results of this study indicated that Padang Padang area were identified 38 bird species. The dominant species were member of the insect, small reptile feeder and member of fruit/seeds feeder, but another member so find that is fish feeder, predator and nectar feeder. Seven species of birds observed on the site were protected by Indonesia Regulation, two species of birds were migrant and four species of birds were endemic species in Indonesia. Threat on birds in this area was illegal capture of birds that economic value to trade.